R-TIK Digital Literacy towards Indonesian MSMEs (UMKM) Digital Energy of Asia - Manik Sunuantari; Irwa Rochimah Zarkasi; Imsar Gunawan; Raihan Muhammad Farhan (Komunikator, 2021)
In accordance with the commitment of the World Summit on the Information Society, it is stated that Small, Medium and Micro Enterprises (SMMEs) are providers of employment for the community.  In Indonesia, SMMEs are known as UMKM (Small, Medium and Micro Enterprises Indonesia). The existence of ICT is considered capable of increasing economic growth as well as providing new employment field during the Covid-19 Pandemic. One way to encourage the rise of UMKM) is through the Indonesian R-TIK (Indonesia ICT Volunteers). The purpose of this research is to determine the involvement of R-TIK in the UMKM Go Online program.  Whereas the theories and concepts used are the Information Society, Digital Literacy and Empowerment of UMKM.  The research method used is a case study, R-TIK with UMKM in Polewali Mandar, West Sulawesi. The results indicate that digital literacy activities carried out by R-TIK together with the Department of Industry, Trade, Cooperatives, and UMKM encouraged the growth of UMKM in Polewali Mandar. The presence of QRen in the UMKM online program has push the pace of the Indonesian economy in the context of realizing Indonesia as a Digital Energy of Asia.